PROBLEMATIQUE DE L’ENSEIGNEMENT DE PHYSIQUE DANS LES CLASSES DE CINQUIEME ANNEE DES HUMAITES SCIENTIFIQUES « cas des quelques écoles de la ville Kisangani de 2014-2015 - BAENDAENDA SHINDANI Depse, (IJRDO- Journal of Educational Research, 2019)
In that study, we havve to know that the teaching of physical sciences is a whole of concepts created by the mind to give to the man a modal in the world and to purchase (to win) the experience in his middle.Thus we must have a special methodology which can turn child up able to developpe himself the creative spirit, the intellectual curiosity, for his preparation on the work exercise or on the upper sudies.So the child can be important to the community. We must reach his pedagogical objectives and institutionnnels imposed by the government to teachers.We must avoid the human order missing (under qualification), material and organization which will allow the teaching of the physical sciences.We cannot speak about these insufficiencies whithout to detect them according to the suitable pedagogical methods.